O curso de pedagogia analisados pelos artigos acadêmicos produzidos entre 1999 e 2011 - Gonçalves, Juliana Henrique (2013)
This research focused on the University courses of pedagogy. Its principal aim was to identify the concept of pedagogy expressed in pre selected articles published between 1999 and 2011. The specific goals are: to map and analyze the articles published in academic journals; to identify the aims of each article; to identify the prospects and criticisms about the course of pedagogy and analyze comparatively convergent and divergent ideas. The method was state of art research. The on-line database of Scielo and CAPES were used to select the 20 articles that were analyzed in this text. The following descriptors were used on this on-line research: pedagogy, course of pedagogy and pedagogue. The research had as reference the guiding legislation of the courses and the theorists: Debesse, Mialaret, Saviani, Libâneo, Cruz, Gentili and Gimeno Sacristán. A difference was noted between the articles written before the publication of the national curriculum guidelines and the produced after it. The conclusion is that the concept of pedagogy is still an open issue full of debates and controversies, especially concerning how the course should be structured